Next steps in the development of ecological soil clean‐up values for metals. (11th September 2013) - Wentsel, Randall; Fairbrother, Anne; Fairbrother, Anne
Abstract This special series in Integrated Environmental Assessment Management presents the results from 6 workgroups that were formed at the workshop on Ecological Soil Levels—Next Steps in the Development of Metal Clean‐Up Values (17–21 September 2012, Sundance, Utah). This introductory article presents an overview of the issues assessors face when conducting risk assessments for metals in soils, key US Environmental Protection Agency (USEPA) documents on metals risk assessment, and discusses the importance of leveraging from recent major terrestrial research projects, primarily to address Registration, Evaluation, Authorization and Restriction of Chemical Substances (REACH) requirements in Europe, that have significantly advanced our understanding of the behavior and toxicity of metals in soils. These projects developed large data sets that are useful for the risk assessment of metals in soil environments. The workshop attendees met to work toward developing a process for establishing ecological soil clean‐up values (Eco‐SCVs). The goal of the workshop was to progress from ecological soil screening values (Eco‐SSLs) to final clean‐up values by providing regulators with the methods and processes to incorporate bioavailability, normalize toxicity thresholds, address food‐web issues, and incorporate background concentrations. The REACH data sets were used by workshop participants as case studies in the development of the ecological standards for soils. The workshop attendees discussed scientific advancements in bioavailability, soil biota and wildlife case studies, soil processes, and food‐chain modeling. In addition, one of the workgroups discussed the processes needed to frame the topics to gain regulatory acceptance as a directive or guidance by Canada, the USEPA, or the United States. Integr Environ Assess Manag 2014;10:342–345. © 2013 SETAC